2020
DOI: 10.1039/d0sm00019a
|View full text |Cite
|
Sign up to set email alerts
|

Engineering interfacial entropic effects to generate giant viscosity changes in nanoparticle embedded polymer thin films

Abstract: We demonstrate a new method to study the viscosity of PNC thin films, consisting of polymer grafted nanoparticles (PGNPs) embedded in un-entangled homopolymer melt films, using atomic force microscopy based force–distance spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 59 publications
1
8
1
Order By: Relevance
“…Clearly, as experimental systems typically incorporate attractions, we conclude that the purely repulsive case does not serve as a good model for understanding the phase and the self-assembly behavior, especially for small NPs. Further, the different conclusions presented in the literature for D = 5 nm NPs must also be reflective of the energetics of the system studied (in that case with a gold core) and not reflective of purely entropic effects. Interestingly, Corbierre et al observed predominantly dispersed gold NPs with only some aggregation for P / N = 40.…”
Section: Resultsmentioning
confidence: 95%
“…Clearly, as experimental systems typically incorporate attractions, we conclude that the purely repulsive case does not serve as a good model for understanding the phase and the self-assembly behavior, especially for small NPs. Further, the different conclusions presented in the literature for D = 5 nm NPs must also be reflective of the energetics of the system studied (in that case with a gold core) and not reflective of purely entropic effects. Interestingly, Corbierre et al observed predominantly dispersed gold NPs with only some aggregation for P / N = 40.…”
Section: Resultsmentioning
confidence: 95%
“…50%, have attracted immense interest due to both their scientific and technological implications. 37–39 Such a high loading of nanoparticles frustrates the packing of matrix chains, which introduces free volume at the molecular level 9,32 and can also be used to generate controllable nanoscale structures and morphology including porosity. 27,28,31,55–57 This, in turn, yields significant control over various material properties like mechanical and transport properties, including stiffness, strength, toughness, modulus, and viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…27,28,31,55–57 This, in turn, yields significant control over various material properties like mechanical and transport properties, including stiffness, strength, toughness, modulus, and viscosity. 3,9,38,39 In particular there has been significant recent interest in utilizing these design aspects to develop high efficiency gas separation 17,30,46,47 and water desalination 14–16,23–26 thin film PNC membranes. Both the free volume and nanoscale porosity could be tuned by controlling the dispersion of nanoparticles in these PNCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, additional parameters such as the size of the NPs and the width of interfacial layer (IL) have been found to influence the viscoelastic properties of the PNCs. [13][14][15][16][17][18] While the structure and dynamics of pristine polymer melts are largely determined by entropic effects in PNCs, a strong enthalpic effect is introduced between the NP and the matrix chains [17][18][19] that strongly alters their structure and dynamics. With polymer-grafted NPs (PGNPs), which are used widely to enhance the dispersion at high loadings in PNCs, an additional entropic effect is introduced due to size mismatch between the graft and matrix chains, even for chemically identical monomers.…”
Section: Introductionmentioning
confidence: 99%